Evidence for discrimination between feeding sounds of familiar fish and unfamiliar mammal-eating killer whale ecotypes by long-finned pilot whales - Cure, Charlotte; Isojunno, Saana; Vester, Heike; Visser, Fleur; Oudejans, Machiel; Biassoni, Nicoletta; Massenet, Mathilde; Beauchesne, Lucie; Wensveen, Paul J; Sivle, Lise D.; Tyack, Peter L.; Miller, Patrick J. O. (Animal Cognition, 2019)
Killer whales (KW) may be predators or competitors of other cetaceans. Since their foraging behavior and acoustics differ among populations (?ecotypes'), we hypothesized that other cetaceans can eavesdrop on KW sounds and adjust their behavior according to the KW ecotype. We performed playback experiments on long-finned pilot whales (Globicephala melas) in Norway using familiar fish-eating KW sounds (fKW) simulating a sympatric population that might compete for foraging areas, unfamiliar mammal-eating KW sounds (mKW) simulating a potential predator threat, and two control sounds. We assessed behavioral responses using animal-borne multi-sensor tags and surface visual observations. Pilot whales barely changed behavior to a broadband noise (CTRL?), whereas they were attracted and exhibited spyhops to fKW, mKW, and to a repeated-tonal upsweep signal (CTRL+). Whales never stopped nor started feeding in response to fKW, whereas they reduced or stopped foraging to mKW and CTRL+. Moreover, pilot whales joined other subgroups in response to fKW and CTRL+, whereas they tightened individual spacing within group and reduced time at surface in response to mKW. Typical active intimidation behavior displayed to fKW might be an antipredator strategy to a known low-risk ecotype or alternatively a way of securing the habitat exploited by a heterospecific sympatric population. Cessation of feeding and more cohesive approach to mKW playbacks might reflect an antipredator behavior towards an unknown KW ecotype of potentially higher risk. We conclude that pilot whales are able to acoustically discriminate between familiar and unfamiliar KW ecotypes, enabling them to adjust their behavior according to the perceived disturbance type